Gas Chromatographic Investigations of Composition of Spent Tyre Pyrolysis Gasoline (Global Journal of Medical Research, 2013)
This paper describes a case study in which multiple analytical techniques were used to identify and characterize the composition of spent tyre pyrolysis gasoline obtained from the tyre pyrolysis process. The objective of the study was to describe the spent tyre pyrolysis gasoline and determine its suitable commercial application. The analytical techniques used for analyses of spent tyre pyrolysis gasoline included gas chromatography-mass spectrometry, gas chromatography with sulfur-chemiluminescence detector and capillary gas chromatography with flame-ionization detector. Examination of the chemical composition of the spent tyre pyrolysis gasoline showed that nearly 90 % of the sample composition is established. Generally, aromatic hydrocarbons and naphthenes are the dominating compounds detected in the spent tyre pyrolysis gasoline obtained from tyres pyrolysis. The content of individual sulfur compounds is also measured. Compared to similar researches only the alkylthiols are identified. The spent tyre pyrolysis gasoline comprise mainly of compounds that are similar to pyrolysis gasoline from naphtha stream cracking, fluid catalytic cracking (FCC) gasoline and straight run naphtha. The spent tyre pyrolysis gasoline has high sulfur content what is a reason to make it directly used inapplicable. The straight run naphtha and pyrolysis gasoline from naphtha stream cracking have lowest content of sulfur and the spent tyre pyrolysis gasoline could be blended with the fluid catalytic cracking (FCC) gasoline for hydrotreatment. Also the spent tyre pyrolysis gasoline could be blended with the straight run naphtha to catalytic reforming unit for further processing.
Keywords: GC - MS; GC - FID; GC - SCD; spent tyre pyrolysis gasoline; pyrolysis gasoline from naphtha stream cracking; straight run naphtha; fluid catalytic cra